Culturally Responsive Teaching: Stories of a First Nation, Métis, and Inuit Cross-Curricular Infusion in Teacher Education (LEARNing Landscapes, 2014)
This paper explores how the work of the infusion of First Nation, Métis, and Inuit traditions, perspectives, and histories at York University’s Faculty of Education Barrie Site unfolds in practice. It also highlights the learning experiences of pre-service teachers, the majority of whom were non-Aboriginal. Using narrative accounts of practice in faculty and practicum classrooms, the authors elaborate on a set of guiding principles to highlight their practical application by demonstrating what their implementation looks like in local school classrooms. They subsequently describe the challenges faced by faculty and pre-service teachers as they moved theoretical knowledge into practical settings.
Keywords: teacher eductaion; practical; theoretical; First Nation; stories